Políticas públicas de informação: o lugar do arquivo público municipal em um polo de inovação - Nogueira, Fernanda Parolo de Mattos (Universidade Federal de São Carlos, 2021)
The city is considered a movement of urbanization and globalization, being the first social instance of the individual and notwithstanding the innovation process. Therefore, when contemplating the local level, it is possible to observe the global, identifying the elements and actors that make up society, which is currently configured as the Technical-Scientific Informational Milieu from the perspective of Milton Santos. Assuming that the Municipal Public Archive is a strategic agent in this composition and for the development of smart cities, Public Policies of Information come to act in strengthening the role of this institution. In this sense, the objective of the present research was to analyze to what extent the “non-construction” of these public policies in Brazil impacts the Archive and, to identify the actors involved in this process. As specific objectives, it was intended to verify the occurrence of these politiques in the historical public archive of the São Carlos city, considered a pole of innovation and with the potential to become a smart city. The research is done in the scope of Information Science, in an interdisciplinary movement to articulate concepts from Archivology, Social Sciences, Public Management, Politics, Computing, among others. Methodologically, it is configured as exploratory and descriptive, based on bibliographic and documentary research, partially using Content Analysis and Hermeneutic-Dialectic Analysis for data analysis. A partial Case Study was carried out at the Municipal Public Archives present at the Fundação Pró-Memória de São Carlos, using documents and records as a source of evidence for data collection. As a theoretical-argumentative basis, the Actor-Network Theory was used considering that it establishes that the different human and non-human actors connect in a network, influencing each other's behavior and configuration. Thus, public information policies are surrounded by the presence of these actors and susceptible to their actions, which defines their creation, implementation and consolidation. The results reveal that at the municipal level the “non construction” of public information policies that is expressed in the absence and non institutionalization of municipal public archives is even more apparent. It was also identified that the institutions of information and culture are not properly incorporated into the discussion about innovation and smart cities, both in academic and professional spheres. As a conclusion, it is pointed out the need to enhance the network of actors who are involved in the construction of public information policies, such as public power, private initiative, organizations, institutions, citizens, other public policies, highlighting the Archive at this juncture, as information agent, public management, citizenship, memory and innovation.
Public information policies: the place of the municipal public archive in an innovation hub
Keywords: Políticas públicas de informação; Arquivo público municipal; Inovação; Cidades inteligentes e humanas; Meio técnico-científico-informacional; Teoria ator-rede; Public policies of information; Municipal public archive; Innovation.smart and human cities; Technical-scientific-informational milieu; Actor-network theory; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::ARQUIVOLOGIA